BALANCED SCORECARD PADA KINERJA PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN PT MURINDA IRON STEEL PROYEK GUDANG GARAM KEDIRI) - Helmiawan, Gessa; Solikah, Mar'atus; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2022)
The research was conducted to determine the impact from the financial perspective, customer perspective, internal business process perspective, as well as growth and learning perspectives on company performance. The technique applied uses the causality technique. Total population of this study 153 employees. The number of samples taken is 60 people. The results of the research processed with the help of the SPSS reveal that the adjusted R Square are 0.552 or 55.2% which means that the magnitude of the influence of Financial Perspective (X1), Customer Perspective (X2), Internal Business Process Perspective (X3) and Growth and Learning Perspective ( X4) on the Company's Performance (Y) is 55.2%, which means it's still there other factors that affect the company's performance by 44.8% but these factors are not analyzed in this study.